2020
DOI: 10.1016/j.envexpbot.2019.103872
|View full text |Cite
|
Sign up to set email alerts
|

The climatic challenge: Which plants will people use in the next century?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 179 publications
(207 reference statements)
0
48
0
Order By: Relevance
“…Exacerbating these problems in the different geographies are the uncertain effects of climate change, which in many countries is expected to lead to increased variability in seasonality, temperatures and precipitations and increased incidence of hurricanes and wildfires [ 89 ]. Climate change is also predicted to severely impact cultivated plants, affecting crop production in specific geographic locations [ 115 ], stripping nutrients from staple crops [ 46 , 116 ] and making WFPs all the more important for food and nutrition security. Although generally highly adaptable and often more drought tolerant than cultivated crops, WFPs, as many useful plants, are also not fully resistant to climate change [ 116 ].…”
Section: The Importance Of Wild Food Plants Todaymentioning
confidence: 99%
See 1 more Smart Citation
“…Exacerbating these problems in the different geographies are the uncertain effects of climate change, which in many countries is expected to lead to increased variability in seasonality, temperatures and precipitations and increased incidence of hurricanes and wildfires [ 89 ]. Climate change is also predicted to severely impact cultivated plants, affecting crop production in specific geographic locations [ 115 ], stripping nutrients from staple crops [ 46 , 116 ] and making WFPs all the more important for food and nutrition security. Although generally highly adaptable and often more drought tolerant than cultivated crops, WFPs, as many useful plants, are also not fully resistant to climate change [ 116 ].…”
Section: The Importance Of Wild Food Plants Todaymentioning
confidence: 99%
“…Climate change is also predicted to severely impact cultivated plants, affecting crop production in specific geographic locations [ 115 ], stripping nutrients from staple crops [ 46 , 116 ] and making WFPs all the more important for food and nutrition security. Although generally highly adaptable and often more drought tolerant than cultivated crops, WFPs, as many useful plants, are also not fully resistant to climate change [ 116 ]. In the past, many WFPs survived major climatic fluctuations, but thematic studies on the implications of future climate change suggest important impacts on the ability of wild species to survive.…”
Section: The Importance Of Wild Food Plants Todaymentioning
confidence: 99%
“…With the increasing human population, we must not be complacent about what we already have (Godfray & al., 2010). We must continually develop a greater variety of crop plants that are adapted to different ecological conditions not only to keep pace with the ever-expanding human population and global environmental changes (Borrell & al., 2020), but also to maintain genetic resources against newly aggressive microbial pathogens.…”
Section: ■ Priorities For the Systematic Biology Communitymentioning
confidence: 99%
“…Nevertheless, the majority of vegetatively propagated 60 crops have sexually reproducing wild progenitors (Miller and Gross, 2011). Improving our 61 understanding of reproductive biology in vegetative propagated perennial crops has potential to 62 address these challenges by enabling a broader range of useful plants to be banked as seed and used 63 in breeding programmes, enhancing conservation and use of genetic diversity (even if this does not 64 conserve specific vegetative genotypes) (McKey et al, 2010;Borrell, Dodsworth, et al, 2019; Several previous studies have found enset germination to be highly variable (0-90% success) 126 (Tesfaye, 1992;Messele, 1994;Diro et al, 2003). The most detailed study to date by Karlsson et al 127 (2013) found 5-55% germination depending on the accession.…”
Section: Introduction 48mentioning
confidence: 99%